Development of the Social Participation Restrictions Questionnaire (SPaRQ) through consultation with adults with hearing loss, researchers, and clinicians: a content evaluation study. (3rd October 2018) - Heffernan, Eithne; Coulson, Neil S.; Ferguson, Melanie A.
Abstract: Objective: This research aimed to evaluate the content of the Social Participation Restrictions Questionnaire (SPaRQ) in terms of its relevance, clarity, comprehensiveness, acceptability to adults with hearing loss, and responsiveness. Design: Cognitive interviews and a subject matter expert survey were conducted. The interview data were analysed using thematic analysis and a taxonomy of questionnaire clarity problems. Descriptive statistics were calculated for the survey data. Study sample: Fourteen adults with hearing loss participated in the cognitive interviews. Twenty clinicians and academics completed the subject matter expert survey. Results: The majority of the SPaRQ content was found to be relevant, clear, comprehensive, and acceptable. However, an important clarity problem was identified: many adults with hearing loss struggled to switch from answering positively worded items (e.g. "I can attend social gatherings") to answering negatively-worded items (e.g. "I feel isolated"). Several subject matter experts found responsiveness difficult to assess. The SPaRQ was amended where necessary. Conclusion: Few hearing-specific questionnaires have undergone content evaluation. This study highlights the value of content evaluation as a means of identifying important flaws and improving the quality of a measure. The next stage of this research is a psychometric evaluation of the measure.